Transcriptome analysis reveals the molecular mechanisms of adaptation to high temperatures in Gracilaria bailinae - Huang, Yongjian; Cui, Jianjun; Wang, Sipan; Chen, Xinyi; Liao, Jiawei; Guo, Youyou; Xin, Rong; Huang, Bowen; Xie, Enyi (Frontiers in Plant Science, 2023)
Global warming causes great thermal stress to macroalgae and those species that can adapt to it are thought to be better able to cope with warmer oceans. Gracilaria bailinae, a macroalgae with high economic and ecological values, can survive through the hot summer in the South China Sea, but the molecular mechanisms underlying its adaptation to high temperatures are unclear. To address this issue, the present study analyzed the growth and transcriptome of G. bailinae after a 7-day exposure to 15°C (LT: low temperature), 25°C (MT: middle temperature), and 35°C (HT: high temperature). Growth analysis showed that the HT group had the highest relative growth rate（RGR = 2.1%） with the maximal photochemical efficiency of PSII (Fv/Fm = 0.62) remaining within the normal range. Transcriptome analysis showed more differentially expressed genes (DEGs) in the comparison between MT and HT groups than in that between MT and LT, and most of these DEGs tended to be downregulated at higher temperatures. The KEGG pathway enrichment analysis showed that the DEGs were mainly enriched in the carbohydrate, energy, and lipid metabolisms. In addition, the genes involved in NADPH and ATP synthesis, which are associated with photosynthesis, the Calvin cycle, pyruvate metabolism, and the citrate cycle, were downregulated. Downregulation was also observed in genes that encode enzymes involved in fatty acid desaturation and α-linolenic acid metabolism. In summary, G. bailinae regulated the synthesis of NADPH and ATP, which are involved in the above-mentioned processes, to reduce unnecessary energy consumption, and limited the synthesis of enzymes in the metabolism of unsaturated fatty acids and α-linolenic acid to adapt to high environmental temperatures. The results of this study improve our understanding of the molecular mechanisms underlying the adaptation of G. bailinae to high temperatures.